Pengaruh Price Discount Dan Bonus Pack Terhadap Impulse Buying: (Survei Pada Konsumen Alfamart di Kota Tasikmalaya) - Fitria Lestari; H. Cece Rakhmat; Depy Muhamad Pauzy (J-CEKI : Jurnal Cendekia Ilmiah, 2022)
This study aims to determine the simultaneous and partial effects between Price Discount and Bonus Packs on Impulse Buying on Alfamart Consumers in Tasikmalaya City. The research method used is a survey method with a quantitative approach. The sampling technique uses a non-probilin sampling method with a sample of 100 people. The data collection technique uses an online questionnaire. The data used is primary data. The analytical tool used in this study is multiple regression using SPSS 24 The results showed that simultaneously the price discount and the bonus pack had a significant effect on impulse buying. Partially, the price discount had a significant effect on impulse buying. Partially, the bonus pack had a significant effect on impulse buying.